Pharmacognostical, physiochemical and phytochemical evaluation of leaf, stem and root of orchid Dendrobium ochreatum - Banerjee, Janmajoy; Chauhan, Neelmani; Dey, Biplab Kumar (Journal of Applied Pharmaceutical Research, 2018)
The present work was aimed to carry out pharmacognosical and phytochemical evaluation of individual root, stem, and leaves of orchid âDendrobium ochreatum.â The plant was sun dried and was grounded to fine powder using mechanical grinder followed by sieving. The fine powder was collected and subjected to different pharmacognostical studies like fluorescence analysis under uv light at different wavelength. Physiochemical parameters were also evaluated of the dried plant parts like ash values, loss on drying. Each part of plant like root, stem and leaves were separated and subjected to extraction using soxhletion using different polarity solvents i,e hexane, chloroform, ethanol in gradient elution technique. All total nine plant extracts were obtained, phytochemical screening revealed the presence of important phytoconstituents like alkaloid, glycoside, saponins etc whereas only chloroform extracts of stem exhibited the presence of steroid/phytosterol.